2014
DOI: 10.1128/aac.01831-13
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Mode of Action and Resistance Development of Cadazolid, a New Antibiotic for Treatment of Clostridium difficile Infections

Abstract: Cadazolid is a new oxazolidinone-type antibiotic currently in clinical development for the treatment of Clostridium difficileassociated diarrhea. Here, we report investigations on the mode of action and the propensity for spontaneous resistance development in C. difficile strains. Macromolecular labeling experiments indicated that cadazolid acts as a potent inhibitor of protein synthesis, while inhibition of DNA synthesis was also observed, albeit only at substantially higher concentrations of the drug. Strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 21 publications
1
54
0
1
Order By: Relevance
“…In contrast, vancomycin (acting on cell wall synthesis) and metronidazole (interacting with DNA metabolism) were weak inhibitors of C. difficile toxin formation in in vitro assays (21,23). Studies addressing the mode of action of cadazolid revealed that it primarily acts as an inhibitor of protein synthesis, while inhibition of DNA synthesis was observed as a weaker additional mode of action as reported in a companion article by Locher et al (30). These findings are in agreement with the inhibitory effect of cadazolid on de novo C. difficile toxin formation as well as the potent activity against linezolid-and fluoroquinolone-resistant strains reported here.…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, vancomycin (acting on cell wall synthesis) and metronidazole (interacting with DNA metabolism) were weak inhibitors of C. difficile toxin formation in in vitro assays (21,23). Studies addressing the mode of action of cadazolid revealed that it primarily acts as an inhibitor of protein synthesis, while inhibition of DNA synthesis was observed as a weaker additional mode of action as reported in a companion article by Locher et al (30). These findings are in agreement with the inhibitory effect of cadazolid on de novo C. difficile toxin formation as well as the potent activity against linezolid-and fluoroquinolone-resistant strains reported here.…”
Section: Discussionmentioning
confidence: 73%
“…In previous studies, we had been unable to generate C. difficile strains with elevated CDZ MICs in vitro by single-step procedures and even in limited-passage experiments (up to 13 serial passages), demonstrating that the strains had a low propensity for resistance development (1). To obtain clones with elevated CDZ MICs for mechanistic analyses, up to 46 alternating passages on agar and in liquid medium were carried out in the presence of gradually increasing CDZ or LZD concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the MIC. The MICs of C. difficile isolates were determined using the Clinical and Laboratory Standards Institute (CLSI)-recommended reference agar dilution method for anaerobes (29) as described previously (1). For the inoculum, single bacterial colonies or cells collected from colonies exhibiting confluent growth (total culture from passage 46 [CDZ45 and LZD46]) were suspended in supplemented brucella broth and approximately 10 4 to 10 5 CFU were spotted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations